2014
DOI: 10.5424/sjar/2014123-5273
|View full text |Cite
|
Sign up to set email alerts
|

Phosphogypsum amendments and irrigation with acidulated water affect tomato nutrition in reclaimed marsh soils from SW Spain

Abstract: Phosphogypsum (PG) is a by-product of the P fertilizer industry usually valorised as amendment for acidic and sodic soils. This work was aimed to study the effects of PG on nutrient uptake by industrial tomato plants in an originally sodic soil. A completely randomized experiment was performed involving two factors: (i) acidification with nitric acid (mimics cleaning techniques in drip irrigation), and (ii) PG rate (equivalents to 0, 20, 60, and 200 Mg ha–1). The highest PG rate resulted in an increased dry ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 44 publications
1
5
0
Order By: Relevance
“…As already mentioned, in the previous reports on the possibility of using PG for fertilizing arable crops, it has often been demonstrated that the use of this waste does not contribute to an increase in the available P in the soil or its content in plants (Ekholm et al 2011, Nayak et al 2011, Quintero et al 2014. The results from our experiment, however, are in line with other authors, according to whom PG can be a significant source of phosphorus for plants (Vyshpolsky et al 2008, Yakovlev et al 2013, Bouray et al 2020.…”
Section: Phosphorus Content and Uptake In Plant Materialssupporting
confidence: 92%
See 1 more Smart Citation
“…As already mentioned, in the previous reports on the possibility of using PG for fertilizing arable crops, it has often been demonstrated that the use of this waste does not contribute to an increase in the available P in the soil or its content in plants (Ekholm et al 2011, Nayak et al 2011, Quintero et al 2014. The results from our experiment, however, are in line with other authors, according to whom PG can be a significant source of phosphorus for plants (Vyshpolsky et al 2008, Yakovlev et al 2013, Bouray et al 2020.…”
Section: Phosphorus Content and Uptake In Plant Materialssupporting
confidence: 92%
“…The literature abounds in various opinions on the effects of phosphogypsum on the content of phosphorus compounds bioavailable to plants in the soil. Many authors point out that PG properties, such as the acidic reaction, high salinity, as well as high calcium content are factors that can significantly limit the availability of this component to plants (Delgado et al 2002, Elrashidi et al 2010, Ekholm et al 2011, Nayak et al 2011, Quintero et al 2014, Bouray et al 2020). The hitherto studies on the possibility of using PG for fertilizing arable crops have often demonstrated that the use of this waste does not contribute to an increase in the available phosphorus forms in the soil and P content in plants (Elrashidi et al 2010, Ekholm et al 2011, Nayak et al 2011, Quintero et al 2014).…”
Section: Phosphorus Content In Soil Materialsmentioning
confidence: 99%
“…Extracts at 1:5, 1:1, or other fixed soil to water ratios are often used in different scientific domains [ 52 77 ]. Regrettably, sometimes the dilution ratio is missing or not clearly stated in reports or articles [ 78 – 81 ] or maybe this ratio, saturation or other, is assumed, e.g., [ 82 – 86 ], compromising or precluding future comparisons and generalization.…”
Section: Justification For Replacing the Saturation Extract In Hypersmentioning
confidence: 99%
“…Copper availability was positively correlated with Olsen P. However, P is known to reduce Cu availability (Quintero et al, 2014). This may reveal that factors related to the available P index, such as SOM, may have some effect on Cu availability.…”
Section: Resultsmentioning
confidence: 92%
“…Furthermore, there is an increased CEC under NT relative to CT likely ascribed to SOM enrichment, which may contribute to an increased adsorption of K. The decreased B availability under NT may be ascribed to the increased SOM under this tillage method because organic matter decreases B adsorption and retention in soils (Sarkar, De, Das, & Mandal, ). Copper availability was positively correlated with Olsen P. However, P is known to reduce Cu availability (Quintero et al, ). This may reveal that factors related to the available P index, such as SOM, may have some effect on Cu availability.…”
Section: Discussionmentioning
confidence: 99%